Cicil Emas Dalam Fikih Muamalah Kontemporer - Nanda Islamiyah; Najla Aisyifa; Erwan Setyanor (PT. AHLAL PUBLISHER NUSANTARA, 2026)
Gold installment schemes have become one of the most popular financial products offered by Islamic financial institutions in Indonesia. This product is designed to facilitate the public in owning gold through installment payments based on sharia principles. However, in practice, gold installment transactions often raise debates regarding their compliance with Islamic law, especially in the context of contemporary fiqh muamalah. Issues such as the object of the contract, payment mechanisms, ownership transfer, and the potential presence of riba, gharar, or other prohibited elements require deeper academic analysis. This study aims to examine gold installment practices from the perspective of contemporary fiqh muamalah and to analyze their conformity with sharia principles. This research uses a qualitative descriptive method with a literature study approach. Data were collected from classical fiqh literature, contemporary fiqh studies, fatwas of the National Sharia Council of the Indonesian Ulema Council (DSN-MUI), and relevant scholarly articles and regulations related to gold installment transactions. The data were analyzed by comparing normative Islamic legal principles with the implementation of gold installment products in Islamic financial institutions. The results of this study indicate that gold installment transactions are permissible in Islamic law under certain conditions, such as clear contracts, fixed prices, transparency in payment terms, and the absence of riba and gharar. The use of murabahah or similar contracts is considered acceptable as long as it complies with sharia guidelines. This study implies that strengthening sharia compliance supervision and increasing public literacy on Islamic financial contracts are essential to ensure the sustainability and legitimacy of gold installment products within Islamic finance. Keywords: contemporary fiqh; gold installment; Islamic finance; murabahah; sharia compliance Abstrak Cicil emas merupakan salah satu produk pembiayaan yang banyak ditawarkan oleh lembaga keuangan syariah di Indonesia. Produk ini bertujuan untuk memudahkan masyarakat dalam memiliki emas melalui sistem pembayaran secara angsuran berdasarkan prinsip syariah. Meskipun demikian, praktik cicil emas masih menimbulkan berbagai perdebatan dari sudut pandang fikih muamalah kontemporer, khususnya terkait keabsahan akad, mekanisme pembayaran, perpindahan kepemilikan, serta potensi unsur riba dan gharar. Oleh karena itu, kajian mendalam diperlukan untuk menilai kesesuaian praktik cicil emas dengan prinsip-prinsip hukum Islam. Penelitian ini bertujuan untuk menganalisis praktik cicil emas dalam perspektif fikih muamalah kontemporer serta menilai kesesuaiannya dengan ketentuan syariah. Metode penelitian yang digunakan adalah metode kualitatif deskriptif dengan pendekatan studi kepustakaan. Data diperoleh dari literatur fikih klasik, kajian fikih kontemporer, fatwa Dewan Syariah Nasional Majelis Ulama Indonesia (DSN-MUI), serta artikel dan regulasi yang relevan dengan pembiayaan cicil emas. Analisis data dilakukan dengan membandingkan konsep normatif hukum Islam dengan praktik cicil emas di lembaga keuangan syariah. Hasil penelitian menunjukkan bahwa praktik cicil emas diperbolehkan dalam Islam dengan syarat terpenuhinya ketentuan akad yang jelas, harga yang tetap, transparansi pembayaran, serta terhindar dari unsur riba dan gharar. Implikasi penelitian ini menegaskan pentingnya penguatan pengawasan kepatuhan syariah dan peningkatan pemahaman masyarakat terhadap akad-akad syariah dalam produk pembiayaan emas. Kata kunci: cicil emas; fikih kontemporer; keuangan syariah; kepatuhan syariah; murabahah